Brain Abscess as Severe Presentation of Specific Granule Deficiency - Leszcynska, Maria; Patel, Bhumika; Morrow, Matthew; Chamizo, Wil; Tuite, Gerald; Berman, David M.; Potthast, Kevin; Hsu, Amy P.; Holland, Steven M.; Leiding, Jennifer W. (Frontiers in Pediatrics, 2020)
Severe invasive infections such as brain abscess in a child should prompt an immune evaluation. Specific granule deficiency (SGD) is a rare morphologic neutrophil granular defect characterized by reduced granules within neutrophils, absence of granule proteins, and bilobed nuclei. Patients are susceptible to invasive bacterial infections and Candida infections. Mutations in CCAT/enhancer binding protein epsilon (C/EBP-ε) are the most commonly described cause of SGD. The dihydrorhodamine assay is a quantitative and qualitative functional test that determines the oxidative burst and killing potential of neutrophils. Herein, we describe two brothers with specific granule deficiency. The index patient had a history of cellultis twice in the first year of life and then presented at 13 months age with fever, leukocytosis, and right sided weakness. A large space occupying brain abscess was diagnosed. He underwent surgical drainage and cultures yielded Staphylococcus aureus. This infection prompted his diagnosis. His older brother had also been healthy but too had had several episodes of cellulitis. His brother too was diagnosed with SGD when family genetic screening was performed. Evaluation of the index patient included a peripheral smear that showed absent neutrophil granule presence. Forward and side scatter of whole blood via flow cytometry revealed a loss granularity of neutrophils. A DHR was performed to rule out functional killing defects. After stimulation with PMA, neutrophils from the index patient displayed three distinct patterns, two with abnormal oxidase production and two with reduced function. Both patients were ultimately diagnosed with SGD and remain on lifelong anti-bacterial prophylaxis. Diagnosis of SGD relies on establishing reduced or absent granularity within neutrophils. Lifelong anti-bacterial and anti-fungal prophylaxis is indicated. Hematopoietic stem cell transplantation has also been curative.